2022
DOI: 10.3389/fphar.2022.828933
|View full text |Cite
|
Sign up to set email alerts
|

A Role of IL-17 in Rheumatoid Arthritis Patients Complicated With Atherosclerosis

Abstract: Rheumatoid arthritis (RA) is mainly caused by joint inflammation. RA significantly increases the probability of cardiovascular disease. Although the progress of RA has been well controlled recently, the mortality of patients with RA complicated with cardiovascular disease is 1.5–3 times higher than that of patients with RA alone. The number of people with atherosclerosis in patients with RA is much higher than that in the general population, and atherosclerotic lesions develop more rapidly in patients with RA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 143 publications
(161 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, RA is associated with accelerated atherosclerosis, an immune-mediated inflammatory process [ 28 ]. The systemic inflammation present in autoimmune diseases like RA [ 29 , 30 ] contributes to the progression of atherosclerosis. Endothelial dysfunction, which is an early pathological process in atherosclerosis, plays a significant role in the increased cardiovascular risk observed in systemic immune diseases, particularly RA.…”
Section: The Interconnected Pathophysiology and Mechanisms Of Stroke ...mentioning
confidence: 99%
“…Furthermore, RA is associated with accelerated atherosclerosis, an immune-mediated inflammatory process [ 28 ]. The systemic inflammation present in autoimmune diseases like RA [ 29 , 30 ] contributes to the progression of atherosclerosis. Endothelial dysfunction, which is an early pathological process in atherosclerosis, plays a significant role in the increased cardiovascular risk observed in systemic immune diseases, particularly RA.…”
Section: The Interconnected Pathophysiology and Mechanisms Of Stroke ...mentioning
confidence: 99%
“…Studies have demonstrated that IL-17 is involved in the pathogenesis of AS [58,59]. IL-17 was highly expressed in atherosclerotic plaques, and the levels of serum IL-17 in patients with AS were significantly higher than those in healthy subjects [34,[60][61][62]. Recently, Li et al reported that IL-17 induced the senescence of VECs [44].…”
Section: Il-17mentioning
confidence: 99%
“…Within its biological effects, IL-17A might promote accelerated atherosclerosis, which is a key extra-articular manifestation of RA ( 73 ). The observation that in the ApoE −/− (apolipoprotein E-deficient) mouse model, which is a model prone to accelerated atherosclerosis, IL-17A blockage reduced the plaque burden, IL-6 levels, G-CSF levels, CXCL1 expression, and macrophage content in the aorta strongly suggests, among many others, a pathogenetic role of IL-17A in the atherogenic process ( 74 ).…”
Section: Il-8 and Il-17 As Key Players In Organ Damage (Cardiovascula...mentioning
confidence: 99%